Reformasi Hukum Lembaga Pemasyarakatan Sebagai Sub Sistem Peradilan Pidana - Muhammad Arif Sahlepi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
The purpose of correctional is to return the assisted citizens to good ones and to prevent them from repeating the deeds. The legal reform package launched by the Indonesian President, Joko Widodo, begins to run as the reforms in the economic sector. People have great hopes for this reform of law. In the package of legal reform, one of them is strengthening the fostering of prison (LP).                The main problem is the over capacity of the assisted citizens in almost all the prisons (LP)  or correctional institution (Rutan) in Indonesia and the problem of guidance systems for the assisted citizens and for the officers in the prison as well. We all know that the capacity of the prisoners in Indonesia has exceeded, and this becomes the problem; therefore, it is no longer a public secret if a prisoner has a lot of money, he becomes like a king in the prison.                With the inclusion of this issue as part of legal reform package, it is expected that there is a significant improvement. Within the set of criminal justice systems, LP as a sub-system has an equally important role with other sub-systems. The LP can no longer be viewed as a Disposal institution. It has been long enough that LP received less serious attention than other sub-systems; so at the time when news about circulation of drugs controlled from within the LP was spreading over, it gets more serious attention portion.                The high demand for criminal offenses on criminal acts such as narcotics, terrorism, morality, corruption, besides murder, will directly affect the rise of the number of prisoners. Moreover, in recent years the booming arrest of narcotics has led to a dramatic increase in the inhabitants of LP. The inhabitants of LP in Indonesia are mostly filled by narcotics actors, both distributors and users and other criminals.